Materialism without matter: the recurrence of subjectivism in object-oriented ontology. Issue 2 (4th May 2017) - Lemke, Thomas
ABSTRACT: 'Object-Oriented Ontology' (OOO) defines a theoretical commitment to thinking the real beyond human experience. It seeks to uncover the true existence of things, favouring concepts of stability, essence, solidity and permanence over notions of flux, relationality, process and contingency. OOO's ambition is to engage with objects in their own terms in order to address what lies beyond rationality, cognition, knowledge and human mastery. This article presents a critical evaluation of this claim. The first part discusses how OOO is closely connected to a broader philosophical perspective known by the name of speculative realism and to its critique of correlationism. The second section analyses the distinctive understanding of objects that OOO puts forward when it claims to attend to the obscurity and autonomy of things. I will then explore OOO's critique of relational and materialist accounts and its fierce rejection of forms of process philosophy and praxeologial accounts. The fourth part critically engages with OOO's appeal to aesthetics and the displacement of ethical and political concerns that it enacts. The final section demonstrates that OOO's promise to break once and for all with subject–object dualism results in a revived form of subjectivism. The attempt to go 'back' to the object, to start all over again by exploring the inner depth of things, ends up in a superficial attitude that proclaims the return to the object while erasing any account of situatedness or contextuality.